201 Suitability for low-dose rivaroxaban based on compass trial: a district general hospital perspective. (4th June 2021) - Asad, Muhammad; Kazi, Sayed Irfan; Gupta, Mehak; Alaguraja, Priyanth; McCaughey, Daniel; Makan, Jayesh
Abstract : Introduction: COMPASS trial has recommended that low-dose rivaroxaban reduces major adverse cardiac and limb events among patients with stable atherosclerotic vascular disease. In the real-world practice, the recommendations from COMPASS trial can be used as a standard to recognise potentially suitable patients. The objective of our study was to establish the cohort of patients identified as COMPASS-eligible for low dose rivaroxaban. Methods: A health service evaluation of Cardiology Outpatients from Shrewsbury and Telford Hospital NHS Trust (SaTH) was carried out. The specific characteristics of the selected cohort included known stable atherosclerotic vascular disease while the inclusion and exclusion criteria incorporated in the COMPASS trial was used as a standard. The SaTH clinical databases from January 2021 were utilized to conduct a retrospective analysis to identify patients who could prospectively benefit from low-dose rivaroxaban. Results: Among the 99 patients who were found to have stable atherosclerotic vascular disease, 34 patients were deemed eligible for low dose rivaroxaban. Patients in our COMPASS-eligible group included 26 patients who were ≥65years of age while 8 patients were noted to be <65 years of age. Further analysis revealed that 94% of the patients had coronary artery disease as compared with only 6% found to have peripheral artery disease. In this cohort of patients, 79 % of the non-eligible patients were excluded due to underlying atrial fibrillation. Conclusion: About one-third of our cohort of patients met the COMPASS criteria and could potentially benefit from low dose rivaroxaban therapy. There is certainly a strong mandate for introduction of rivaroxaban following the COMPASS trial recommendations. Local protocols should be established to ensure that this window of opportunity to prevent major adverse cardiovascular and limb events is not missed in the clinical practice. Conflict of Interest: None